Challenges of Work-Life Balance of Nurses Working in Hospitals of Haridwar Region (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This review paper aims to explore the challenges faced by nurses in achieving work-life balance within hospital settings in the Haridwar district. Work-life balance is crucial for the well-being and job satisfaction of nurses, ultimately impacting the quality of patient care. In the context of nursing, achieving work-life balance is paramount not only for the health and happiness of individual nurses but also for the quality of patient care they provide. Moreover, the significance of work-life balance extends beyond individual nurses to the healthcare system as a whole. A workforce that is overburdened, fatigued, or demoralized due to work-related stressors is less likely to be engaged, productive, or committed to their roles. Through an extensive review of literature, this paper identifies and analyzes various factors contributing to the imbalance between work and personal life among nurses in Haridwar hospitals. Additionally, potential solutions and recommendations to address these challenges are discussed to improve the overall work environment and enhance the quality of nursing care.